Automated water consumption control system in nitric acid production - Puhanovskyi, Oleh; Puhanovskyi, Kyrylo (CPN Publishing Group, 2024)
The paper proposes a variant of the water flow control system used for irrigation of the absorption column in the production of nitric acid. The proposed solution was developed for industri - non-concentrated nitric acid. Modern specialized devices and microprocessor controllers were used to create the control system. A model of the control system was created during the development. Based on the model, basic controller settings were found, which will be useful when implementing the system in production.
Keywords: nitric acid; industrial control; Simulink; industrial automation; microcontroller